The ideology of Transcendental in contemporary feminist Art - Kareem Mohsen Ali Sameer Al Kabi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The research of the term "The Ideology of Transcendental in contemporary feminist Art" is divided into four chapters. The first chapter deals with the methodological framework of the research. The problem of the research ended with the following question: What is The Ideology of Transcendental in contemporary feminist Art? It also included the objective, importance and need of research. The second chapter dealt with two topics. The first was titled Feminist Movement in Thought and Literature, while the second dealt with contemporary feminist Art. While the third chapter was devoted to research procedures. The researcher chose (3) works in an intentional manner and was analyzed using the descriptive method (qualitative content analysis method) based on theoretical framework indicators. The fourth chapter is devoted to the research results Among them were the following: 1. The ideology of Transcendental in the contemporary feminist Art is manifested through the adoption of new artistic methods by women artists, such as the method of processing, and the adoption by women of the requirements of the present era. 2.feminist Art represents explicit and lofty ideologies that advocate women’s freedom and call for the elimination of all forms of violence and changing the prevailing inferiority. As for the conclusions, 1- contemporary feminist Art is an overarching ideology for women at the expense of the subjective aspect. Despite the call for freedom and the call for recognition and status of women, the women’s figure revealed an eternal reality of secondary women following the same man. This signifies the neglect of the image of the iconic woman from the woman artist, and the confiscation of women’s efforts by women as well. 2-The image of supremacy in contemporary feminist art has emerged through the dedication of emotional images that reveal psychological burdens living in the memory of women related to their search for love, giving and good behavior, overcoming all obstacles and barriers that stand against women’s existence. The research ended with recommendations, proposals and a list of sources.